Port Reform Toolkit : Effective Decision Support for Policymakers, Module 1. Framework for Port Reform - Public-Private Infrastructure Advisory Facility (Washington, DC: World Bank, 2013)
This Port Reform Toolkit, consisting of eight modules, presents background information, concrete examples, and specific tools and methods that public officials can use to make effective, sustainable reforms of public institutions that provide port services in developing countries. In particular it focuses on understanding the needs, challenges and risks for sector reform; choosing among options for private sector participation and analyzing their implications; preparing legislation, contracts and institutional charters to govern private sector participation; managing the transition to increased private sector involvement. The Toolkit presents "best international practices" in a manner that is relevant to decision-makers. The Toolkit is designed to be easily understood by non-specialists. Thus, it attempts to make general points with concrete examples. It is illustrated with experience drawn from recent port reform activities around the world.